From Entrepreneurial Intention to Venture Creation: Leveraging Inclusive Sociopreneurship to Strengthen Student Entrepreneurship in Semarang - Wijang Sakitri; Jarot Tri Bowo Santoso; Nimas Aulia Pambajeng Miftahunnajah (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This study seeks to advance inclusive and sustainable entrepreneurship through a sociopreneurship-based approach among prospective student entrepreneurs by strengthening capabilities in marketing, branding, business strategy, and financial management. Method: A participatory action framework was applied, involving observation, training, focus group discussions, internships, apprenticeships, and mentoring with selected partners. Data were collected through interviews, direct observation, and daily reports, and analysed using qualitative descriptive methods with triangulation. Practical Applications: The results highlight the relevance of an inclusive, sociopreneurship-oriented entrepreneurship model that supports higher education institutions in fostering competence development and translating entrepreneurial intention into meaningful action. Conclusion: The program enhanced students’ competencies, networks, and entrepreneurial commitment, while facilitating the practical realisation of business initiatives, thereby contributing to the emergence of new entrepreneurs.